2021
DOI: 10.1016/j.eclinm.2021.101069
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of pulmonary tissue factor, loss of thrombomodulin and immunothrombosis in SARS-CoV-2 infection

Abstract: Background: SARS-CoV-2 infection is associated with thrombotic and microvascular complications. The cause of coagulopathy in the disease is incompletely understood. Methods: A single-center cross-sectional study including 66 adult COVID-19 patients (40 moderate, 26 severe disease), and 9 controls, performed between 04/2020 and 10/2020. Markers of coagulation, endothelial cell function [angiopoietin-1,-2, P-selectin, von Willebrand Factor Antigen (WF:Ag), von Willebrand Factor Ristocetin Cofactor, ADAMTS13, thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
90
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(103 citation statements)
references
References 81 publications
11
90
2
Order By: Relevance
“…Here, we demonstrated that the incubation of HLMVEC with cytokines released by spike-treated macrophages actually causes a huge increase in the expression of the tissue factor (TF), undetectable under control conditions and a concomitant significant decrease in the expression of the anti-thrombotic thrombomodulin. Our findings are in line with the recent study by Francischetti et al, which illustrates a normal expression of thrombomodulin in the alveolar capillaries of control cases and the loss of the protein in COVID-19 patients [53]; as suggested by the authors, an upregulation of pulmonary TF with the loss of thrombomodulin emerge as a potential link to immunothrombosis in COVID-19.…”
Section: Discussionsupporting
confidence: 93%
“…Here, we demonstrated that the incubation of HLMVEC with cytokines released by spike-treated macrophages actually causes a huge increase in the expression of the tissue factor (TF), undetectable under control conditions and a concomitant significant decrease in the expression of the anti-thrombotic thrombomodulin. Our findings are in line with the recent study by Francischetti et al, which illustrates a normal expression of thrombomodulin in the alveolar capillaries of control cases and the loss of the protein in COVID-19 patients [53]; as suggested by the authors, an upregulation of pulmonary TF with the loss of thrombomodulin emerge as a potential link to immunothrombosis in COVID-19.…”
Section: Discussionsupporting
confidence: 93%
“…The formation of NETs in the lungs and bloodstream can be critically associated with thrombosis ( 95 ). Platelet activation and endothelial cell damage ( 96 , 97 ) in COVID-19 patients are also resulting in elevated levels of extracellular vesicles (EVs) ( 98 100 ) expressing tissue factor ( 101 , 102 ) and associated with severity of disease ( 99 , 101 , 103 ).…”
Section: Discussionmentioning
confidence: 99%
“…From our analysis of their raw data, we conclude that the sample set and experimental design implemented in Mast et al are fundamentally flawed. The concerns are significantly magnified knowing that others researching COVID-19 are citing these poorly substantiated results in publications ( Francischetti et al, 2021 ) or integrating these findings into their experimental design and future plans.…”
Section: Discussionmentioning
confidence: 99%